Phanerozoic orogeny in the South China Block traced by clastic components from Cambrian to Triassic sedimentary rocks. (15th August 2021) - Shen, Linwei; Yu, Jin-Hai; Griffin, W.L.
Graphical abstract: Highlights: Four groups of detrital zircon age spectra were identified in the Yong'an basin. Three changes of clastic components correspond to Phanerozoic orogeneses in the SCB. Late Paleozoic orogeny in the eastern SCB could be more extensive. Abstract: Systematic detrital zircon U-Pb dating was applied to Cambrian to Triassic sedimentary rocks in the Yong'an basin, southeastern South China, and yields four age groups. Cambrian and Ordovician quartz schists display prominent Grenvillian (906–1199 Ma) and minor late Neoarchean to earliest Paleoproterozoic (2418–2619 Ma) populations, showing characteristics of an East Gondwanan origin. Devonian and Carboniferous sandstones feature euhedral Neoproterozoic (733–999 Ma) and early Paleozoic (405–468 Ma) detrital zircons, suggestive of a proximal accumulation sourced from the nearby Wuyi terrane. Middle Permian to early Triassic sandstones contain abundant late Paleoproterozoic (1743–1979 Ma), Grenvillian (893–1271 Ma), and early Paleozoic (403–471 Ma) detrital zircons, together with increasing late Paleozoic (264–374 Ma) populations, indicating multiple provenances. Late Triassic sandstones show dominant proportions of late Paleoproterozoic (1805–1938 Ma) zircons, derived mainly from the Wuyi terrane. Three Phanerozoic orogenic events in the South China Block (SCB), i.e. early Paleozoic (Kwangsian or Wuyi-Yunkai), late Paleozoic, and early Mesozoic (Indosinian) orogenies, probably are responsible for the changes in clastic provenance among the four groups of sedimentary rocks. The late Paleozoic orogeny in the SCB was previously thought to be a limited minor event. This study suggests that the impact of late Paleozoic orogenesis on the SCB could be much wider. The uplift of the Wuyi Mountains probably started after the early Paleozoic orogeny, much earlier than previously proposed, and has provided long-term clastic supply to the Yong'an basin and nearby basins.